(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
The study investigated on soil nutrients in agriculture practiced high, medium high, medium low and low land at Kalihati upazila of Tangail district during October 2017 to June 2018. Thirty soil samples were collected from different land types at the study area and analyzed at Soil Resource Development Institute (SRDI) to determine soil nutrient status. The soil parameters under investigation included pH, organic matter (OM), total nitrogen (N), available phosphorus (P), available zinc (Zn), available iron (Fe), available manganese (Mn), available boron (B), exchangeable potassium (K), exchangeable calcium (Ca) and exchangeable magnesium (Mg). Results indicated that many of the soil nutrient levels decreased such as pH (5.63 to 6.40), P (3.50 to 23.20 μg g-1), Zn (3.27 to 3.60 μg g-1), Mn (21.12 to 57.90 μg g-1), B (0.17 to 0.60 μg g-1), K (0.18 to 0.30 meq 100g-1) and Ca (5.75 to 9.10 meq 100g-1). On the contrary, the average content of OM (2.30 to 1.40%), Fe (248.22 to 161.10 μg g-1) and Mg (2.07 to 1.80 meq 100g-1) were increased. Total N content status did not change much (0.12%). Soil nutrients like those that available Zn, Fe, Mn and Mg contents were found above optimum level (very high) but OM and N status found below optimum level (low, very low and medium). Nutrient concentrations below optimum levels may limit crop yield. Updated knowledge about soil nutrient status needs to be provided for the farmers so that they can use necessary amount of fertilizers and avoid applying excess amount of fertilizers. Int. J. Agril. Res. Innov. Tech. 10(2): 84-90, December 2020